Hand Arm Vibration Exposure Of The Chainsaw Machine - Gurasekeran, Prakash (Universiti Sains Malaysia, 2005)
This project presents experiment results of the hand arm vibration transmitted from the chainsaw. The vibration emitted from the chainsaw taken at front and rear handle for three biodynamic axes which represents in accordance with ISO 5349 (1986). For this purpose, three operational modes were implemented; idling, racing and cutting based on ISO 7505 (1986). Idling and racing does not involve any contact with the logs while cutting operation is carried out at 2 direction; vertical and horizontal cutting. Vertical (bucking) and horizontal (felling) cutting techniques were adopted from forestry work. For vertical cutting, initial steps involved logs positioned horizontally on a work bench and clamped at both sides to prevent movement. Cutting operations were done at 3 different angles; 0°, 30° and 45°. For each angle, vibration measurements were done in 3 different speed of rotating chain/cutter; 750 rpm, 980 rpm, and 1220 rpm. The vibration measurements were obtained in the form of frequency-weighted acceleration, given in ms-2 using integrating vibration meter. Similar steps were followed for horizontal cutting where logs were positioned vertically prior to cutting. For idling operation, the dominant axis was the z axis with value of 14.7 m/s2 which occurred in rear handle. For the second operation or the racing operation the dominant axis was the x axis wit value of vibration of 18.7 m/s2 occurred at front handle of the chainsaw. In cutting operation, the value of vibration does not depend only on cutting speed. The values of the hand arm vibration are also influenced by factors such as angle, logs condition and few others. Knowledge of vibration acceleration value may increase the understanding of vibration transmission from forestry machinery such as chainsaw to human hand and aid in the development of effective isolation devices.